Review artikel: Metode Analisis obat Tuberkulosis Dalam Plasma Darah - Datu Muhammad Cordova; Shiyami Aulia Nur Darmawan; Mutiara Alfiyah; Marsah Rahmawati Utami; Lina Nurfadhila (Journal of Pharmaceutical and Sciences, 2023)
Tuberculosis is a respiratory disorder that is contagious and is caused by an infection with the bacterium Mycobacterium tuberculosis (aerobic bacteria). Treatment of tuberculosis usually uses first-line drugs, namely isoniazid, rifampicin, ethambutol and pyrazinamide. The purpose of this study was to review the effectiveness of developing HPLC or UPLC methods with UV and MS detectors to review tuberculosis drug concentrations in biological blood plasma samples. The author's search method in compiling the results of a journal review regarding the development of methods for analyzing anti-tuberculosis drugs (OAT) in biological blood samples using databases from Google Scholar and Pubmed®. A total of 26 relevant journals will be used for discussion in the journal review. The results obtained are the most widely used method in the analysis of OAT using HPLC/UPLC mass and ultraviolet detectors in a biological sample, blood plasma. It has been reported in several studies that the UPLC method has increased sensitivity as indicated by a decrease in LOD and LOQ values compared to the HPLC method.